Review of Raphael Greenberg and Yannis Hamilakis, Archaeology, Nation, and Race. Confronting the Past, Decolonizing the Future in Greece and Israel - Lalaki, Despina (Historein, 2025)
Review of Raphael Greenberg and Yannis Hamilakis. Archaeology, Nation, and Race. Confronting the Past, Decolonizing the Future in Greece and Israel. New York: Cambridge University Press, 2022.